2015
DOI: 10.1136/jech-2014-205171
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in smoking cessation in 11 European countries from 1987 to 2012

Abstract: Socioeconomic inequalities in smoking cessation rates have strongly increased since the 1990s and during the 2000s. This suggests that the tobacco control policies implemented during the 2000s have not been able to counter the trend in increasing inequalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 31 publications
8
71
1
1
Order By: Relevance
“…88 Cessation programmes have not always been effective, benefitting some groups more than others. 89,90 The findings from our review show that time-discounting can potentially help epidemiologists, policy-makers and public health practitioners understand these trends and develop interventions that can tackle such issues. First, interventions which assume a flat rate of discounting across population groups may fail to capture smokers' perception of costs and benefits over time.…”
Section: Discussionmentioning
confidence: 92%
“…88 Cessation programmes have not always been effective, benefitting some groups more than others. 89,90 The findings from our review show that time-discounting can potentially help epidemiologists, policy-makers and public health practitioners understand these trends and develop interventions that can tackle such issues. First, interventions which assume a flat rate of discounting across population groups may fail to capture smokers' perception of costs and benefits over time.…”
Section: Discussionmentioning
confidence: 92%
“…5 However, as suggested by some studies, because the rates of smoking cessation are lower in socioeconomically vulnerable populations, the differences in smoking rates between socioeconomic levels may have increased. 6,7 Several variables relating to sociodemographic conditions are closely connected with the likelihood of smoking behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Because of that relationship may be a reflection of the smoking epidemic, the analysis was adjusted for time as it has been done in other previous studies (Agaku et al, 2014;Bosdriesz, Willemsen, Stronks, & Kunst, 2015). In view of the fact that previous studies in Spain and in Ireland reported that smoking trends had changed substantially after the introduction of smokefree legislation (Brugha et al, 2009;Regidor et al, 2011), this relationship was addressed in two ways: firstly, by focusing on the period preceding the introduction of comprehensive smoke-free legislation in January 2006; and secondly, the relationship between tobacco prices and the quit ratio was calculated for the entire study period, adjusted for trend and the presence or absence of the law.…”
Section: Methodsmentioning
confidence: 99%